2021
DOI: 10.3390/ijms22094602
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Histochemistry of Seed Coat Development of Wild (Pisum sativum subsp. elatius (M. Bieb.) Asch. et Graebn. and Domesticated Pea (Pisum sativum subsp. sativum L.)

Abstract: In angiosperms, the mature seed consists of embryo, endosperm, and a maternal plant-derived seed coat (SC). The SC plays a role in seed filling, protects the embryo, mediates dormancy and germination, and facilitates the dispersal of seeds. SC properties have been modified during the domestication process, resulting in the removal of dormancy, mediated by SC impermeability. This study compares the SC anatomy and histochemistry of two wild (JI64 and JI1794) and two domesticated (cv. Cameor and JI92) pea genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…In our study of chickpea seeds we observed the light line, the presence of which was confirmed also in cultivated and wild pea genotypes. However, the light line of wild pea genotypes was more pronounced [61], which cannot be unambiguously stated for wild chickpea. A light line that lays within the macrosclereids was interpreted variously, but its main purpose is not yet clarified [61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In our study of chickpea seeds we observed the light line, the presence of which was confirmed also in cultivated and wild pea genotypes. However, the light line of wild pea genotypes was more pronounced [61], which cannot be unambiguously stated for wild chickpea. A light line that lays within the macrosclereids was interpreted variously, but its main purpose is not yet clarified [61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 81%
“…Lipidic compounds stained with Sudan Red mostly occur in the cuticle on the surface of the seed coat of chickpea, which is similar to pea [25,61], with a strong signal observed in middle and basal parts of the macrosclereid cells. In addition, nearly mature pea seeds had signal above the light line [61] that can be observed in some chickpea lines.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations